2019
DOI: 10.18590/euscorpius.2019.vol2019.iss277.1
|View full text |Cite
|
Sign up to set email alerts
|

Trypanothacus gen. n., a new genus of burrowing scorpion from the Arabian Peninsula (Scorpiones: Buthidae)

Abstract: Euscorpius is the first research publication completely devoted to scorpions (Arachnida: Scorpiones). Euscorpius takes advantage of the rapidly evolving medium of quick online publication, at the same time maintaining high research standards for the burgeoning field of scorpion science (scorpiology). Euscorpius is an expedient and viable medium for the publication of serious papers in scorpiology, including (but not limited to): systematics, evolution, ecology, biogeography, and general biology of scorpions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In bothriurid scorpions, the rate of evolution of hemispermatophore structures varies, and parts deemed essential for sperm transfer may be more conserved by stabilizing selection and relay more phylogenetic signal (Mattoni et al, 2012). In buthids, we have found that as a rule, capsule and lobe structure tends to be well conserved in species belonging to the same genus (e.g., Kovařík et al, 2018a;Lowe, 2010bLowe, , 2018Lowe et al, 2014Lowe et al, , 2019. Across a major clade, the 'Buthus' group, we have not found differences in capsule shape as profound as those between G. madagascariensis and 'hirtus' groups.…”
Section: Hemispermatophorementioning
confidence: 79%
See 1 more Smart Citation
“…In bothriurid scorpions, the rate of evolution of hemispermatophore structures varies, and parts deemed essential for sperm transfer may be more conserved by stabilizing selection and relay more phylogenetic signal (Mattoni et al, 2012). In buthids, we have found that as a rule, capsule and lobe structure tends to be well conserved in species belonging to the same genus (e.g., Kovařík et al, 2018a;Lowe, 2010bLowe, , 2018Lowe et al, 2014Lowe et al, , 2019. Across a major clade, the 'Buthus' group, we have not found differences in capsule shape as profound as those between G. madagascariensis and 'hirtus' groups.…”
Section: Hemispermatophorementioning
confidence: 79%
“…When genera reach a critical mass or become heterogeneous, analysis is warranted to identify putative lineages for splitting into smaller taxonomic units that better encode phylogeny and ecological or evolutionary developments. Our recent work has addressed this for some buthid genera: Babycurus Karsch, 1886(Kovařík et al, 2018b, Butheolus (Lowe, 2018) and Buthacus Birula, 1908Lowe et al, 2019). We diagnosed new genera by identifying consistent differences in previously overlooked external characters and by comparing hemispermatophore capsule structures.…”
Section: Introductionmentioning
confidence: 99%
“…The limits of Buthacus with respect to several other psammophilous Palearctic buthid genera, e.g., Buthiscus Birula, 1905, Liobuthus Birula, 1898, Pectinibuthus Fet, 1984, Plesiobuthus Pocock, 1900, and Vachoniolus Levy et al, 1973, also remains unclear (Kovařík et al, 2013(Kovařík et al, , 2016Lowe et al, 2019;Alqahtani and Badry, 2020). For example, Kovarik et al (2016: 2) suggested, without presenting any phylogenetic evidence, that Buthacus might be a paraphyletic FIGURE 3.…”
Section: Taxonomic Historymentioning
confidence: 99%
“…The scorpion fauna of this region, particularly Israel, the Palestinian territories, and the Sinai Peninsula, was well studied by Gershom Levy and Pinchas Amitai in the 1970s, culminating in the contributions of Levy et al (1973) and Levy and Amitai (1980). Various updates were provided subsequently (Vachon and Kinzelbach, 1987;Amr et al, 1988Amr et al, , 2015Amr and El-Oran, 1994;Kabakibi et al, 1999;Kovařík, 2001Kovařík and Whitman, 2004;Shehab et al, 2011;Amr, 2015;Saleh et al, 2017;Badry et al, 2018;Lowe et al, 2019;Amr et al, 2021). Prior to the present study, five infrageneric taxa of Buthacus, including several synonyms, were recognized from the Levant: Buthacus arenicola (Simon, 1885); Buthacus leptochelys (Ehrenberg, 1829); Buthacus leptochelys nitzani Levy et al, 1973;Buthacus macrocentrus (Ehrenberg, 1828); and Buthacus yotvatensis Levy et al, 1973. Based on new collections, a reassessment of the morphology (including multivariate statistical analysis), and a phylogenetic analysis of morphological and DNA sequence data from two nuclear and three mitochondrial gene loci, published elsewhere (Cain et al, in press), seven species of Buthacus are now recognized from the region (figs.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative morphology of buthid hemispermatophores was pioneered by Vachon (1940Vachon ( , 1952, and although less studied than hemispermatophores of some other scorpion families, can provide informative taxonomic characters at the genus level (e.g., Botero-Trujillo & Flórez, 2011;Esposito et al, 2017;Francke & Stockwell, 1987;Kovařík et al, 2016cKovařík et al, , 2018bLevy & Amitai, 1980;Lowe, 2018;Lowe et al, 2019). The hemispermatophores of 'Grosphus' group scorpions have not been characterized in detail.…”
Section: Hemispermatophorementioning
confidence: 99%